Education, Knowledge and Nutritional Status of Elderly in Elderly Integrated Service Post Working Area of Bentiring Community Health Center Bengkulu - Nurul Khairani; Santoso Ujang Effendi; Desi Kurnia Putri (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
This study was based on the still high nutrient deficiency of elderly in the working area of Bentiring Community Health Center Bengkulu. This study aimed to study the relationship between education and knowledge with nutritional status of elderly in Elderly Integrated Service Post working area of Bentiring Community Health Center Bengkulu. The research type was Analytical Survey and the desain of research was Cross Sectional. The population of this study was all elderly who visited Elderly Integrated Service Post in the working area of Bentiring Community Health Center Bengkulu in January to April 2017 which amounted to 52 elderly. Sampling technique in this research used Total Sampling. The data collected in this study used primary data and secondary data with data analysis technique done by univariate and bivariate analysis with Chi-Square test (c²) through SPSS 16 program. The result of this research were : from 52 elderly, there were 35 elderly (67,3%) with basic education, 27 elderly (51,9%) who had less knowledge, 20 elderly (38,5%) had less nutritional status, there was significant relationship between education with nutritional status of elderly with medium category, and there was a significant relationship between knowledge with nutritional status of elderly with close category. It was expected to Bentiring Community Health Center Bengkulu to improve health services to the elderly by providing nutrition education and medical examination for elderly. Keywords : education, elderly, knowledge, nutritional status, elderly